2016
DOI: 10.4102/apsdpr.v4i4.147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Nigeria’s Achievement of the Millennium Development Goals (MDGs): DETERMINANTS, DELIVERABLES, AND SHORTFALLS

Abstract: Millennium Development Goals (MDGs) was implemented in 2000 ostensibly to accelerate development within its 15 years plan of action. In the credence of this notion, Nigeria was one of the early countries that adopted the rational policy. Prior to the introduction of MDG, the country had implemented diverse developmental policies which are said not to have delivered the expected dividend. Hence, no sooner, the MDGs came to an end; the impulse of another developmental goal became necessary. Sustainable developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Many studies have shown a relatively high maternal mortality rate in Nigeria, 14 , 27 , 28 with the latest National Demographic Health Survey of 2013 of 576 per 100,000 live births showing a 57% reduction from the baseline, as against the 75% MDG target. 9 A more concerted effort is needed in the implementation of already existing policies on reduction of maternal mortality if we are to meet the SDG target of reducing the maternal mortality rate to <70/100,000 live births by 2030. 10 This study showed that hypertensive disorders of pregnancy were the most common cause of maternal deaths, which occurred mostly in the third trimester, followed by puerperal sepsis and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown a relatively high maternal mortality rate in Nigeria, 14 , 27 , 28 with the latest National Demographic Health Survey of 2013 of 576 per 100,000 live births showing a 57% reduction from the baseline, as against the 75% MDG target. 9 A more concerted effort is needed in the implementation of already existing policies on reduction of maternal mortality if we are to meet the SDG target of reducing the maternal mortality rate to <70/100,000 live births by 2030. 10 This study showed that hypertensive disorders of pregnancy were the most common cause of maternal deaths, which occurred mostly in the third trimester, followed by puerperal sepsis and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…For its monitoring and measurement, regular reliable data on mortality by age, sex, and cause, strengthening of civil registration, and vital statistics systems are needed in all countries. 10 However, with the previous targets for the MDGs not met in Nigeria, 9 we are not likely to achieve these new SDG targets. It is against this background that this study reviews the causes of death and any associated risk factors in WRA in Port Harcourt, Nigeria.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…e MDGs which started in 2000 did not however commence in Nigeria until 2005 a er the cancellation of the debt relief in favour of the country. e cancellation of the debt enabled the government to save about US$1 billion annually (Durokifa and Abdul-wasi 2016). During the era of the implementation of the MDGs in Nigeria, a number of steps were taken that included the release of funds to carry out some propoor interventions programmes such as, the Conditional Cash Scheme, National Economic Empowerment and Development Strategy (NEEDS), etc.…”
Section: Implementation Of Sdgs In Nigeriamentioning
confidence: 99%
“…This situation, according to Salami, et al (2016), is detrimental to a country's health performance (in Mavodza, 2017) and to achieving its Universal Health Coverage. The health situation in Nigeria remains dire with unacceptably high health outcome indicators and uncertainty about achieving the SDGs (WHO, 2018) even as it is reported that the country did not meet any of the Millenium Development Goals (Durokifa & Abdul-Wasi, 2016;). Nigeria's health sector human resource challenges have assumed a systemic and critical dimension as it faces healthcare workforce shortage in quantity, quality, right mix and an uneven distribution that result in poor healthcare delivery.…”
Section: Introductionmentioning
confidence: 99%